CORPORATE GOVERNANCE DAN PROFITABILITAS TERHADAP EARNINGS MANAGEMENT PADA PERUSAHAAN NON-KEUANGAN - Nufus, Hayaatun; Almalita, Yuliani (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
The purpose of this study was to determine whether there was an effect of managerial ownership, firm size, leverage, institutional ownership, board of commissioner, audit committee, firm age, and profitability as independent variable on earnings management as the dependent variable in non-financial companies that listed on the Indonesia Stock Exchange. This research using a Discretionary Accruals which are calculated using the Modified Jones Model. This research used companies listed in non-financial company sectors in Indonesia Stock Exchange on 2019 until 2021 and there were 116 companies with a total data 348 that meet the criteria using a purposive sampling method. This research uses multiple regression method for data analysis. The result of this research shows that profitability has positive effect on earnings management. The result of leverage has a positive effect on earnings management. Managerial ownership, firm size, leverage, institutional ownership, board of commissioners, audit committee, and firm age have no effect on earnings management.